Bench Mark Survey Reports on Pounta Block-Himachal Pradesh Bhadson Block-Punjab and Bhathat Block-Uttar Pradesh - Planning Commission (Planning Commission, 1957)
The results of the Bench-Mark Survey have so far been made available in the form of detailed reports for individual blocks. Each report, besides presenting the statistical data for the block contains a detailed discussion on it. Four such reports, relating to the Kolhapur and Morsi blocks of Bombay, the Batala block of Punjab and the Bhadrak block of Orissa, have been published. It is now felt that it will be preferable to present the statistical data for each block with a brief commentary on the most important findings. This procedure, while it gives all the important statistical data, will make possible speedier publication of the reports. Further, reports of two or three blocks have been combined for inclusion in a single volume. The reports for the remaining 14 blocks in which the survey was carried out in 1954 will thus be published in five volumes.
Government of India Planning Commission Programme Evaluation Organisation
Government of India Planning Commission Programme Evaluation Organisation